Curcumin Supplementation in Semen Extender Improves Post-Thaw Quality and Antioxidant Capacity of Gir Bull Spermatozoa - Vala, Sagar B.; Vala, Karsan B.; Solanki, Gajendra B.; Singh, Vivek Kumar; Parmar, Kiran H. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This investigation was carried out on semen of three Gir bulls at Cattle Breeding Farm, Junagadh (India) for a period of 6 months. The aim was to assess the effect of different concentrations of Curcumin, viz., 0 µM (Control), 5 µM, 10 µM, and 15 µM in Andromed extender on sperm quality along with oxidative stress parameters of cryopreserved semen. Semen ejaculates (n=30, 10/bull) with >70% initial motility were included in the study. Soon after initial evaluation, the semen was extended in Andromed extender @ 80 million sperm per ml and was divided into four equal aliquots. The Curcumin stock solution (10 mM) was added in these aliquots to get a final concentration of 0, 5, 10, and 15 µM and sperm motility was checked. It was soon filled and sealed in medium French straws (0.5 ml), equilibrated at 4°C for 4 h and frozen in LN2 vapour using conventional wide mouth freezer. Thawing of straws was done next day in water bath at 37°C for 30 seconds, and various sperm quality parameters including oxidative markers were assessed. The results showed that supplementation of Curcumin to freezing extender improved semen quality and antioxidant capacity. The post-thaw sperm motility, sperm viability, HOST reactive sperm and acrosomal integrity in semen extended with 15 µM Curcumin concentration (57.33±0.67, 73.20±1.05, 64.77±1.56 and 72.43±1.38 %, respectively) were significantly (p
Keywords: Curcumin; Cryopreservation; Gir bull semen; Oxidative markers; Sperm quality parameters